Impacto de tempestade geomagnética na ionosfera e no posicionamento com GNSS: estudo de caso para 20 de novembro de 2003 na região brasileira - Matsuoka, Marcelo Tomio; Collischonn, Carolina; Klein, Ivandro; Camargo, Paulo De Oliveira [UNESP]; Stuani Pereira, Vinicius Amadeu [UNESP] (Univ Federal Parana, Centro Politecnico, 2013)
The goal of this paper is to analyze the influence of the intense geomagnetic storms in the ionosphere and GNSS (GPS) positioning. It was analyzed the effects of intense geomagnetic storm of November 20th 2003 using GPS data from RBMC (Brazilian Network for Continuous Monitoring) located in different sites in the Brazilian region and ionosphere global maps. While analyzing the results, it can be observed an increase in the electron density of the ionosphere in the regions near to the geomagnetic equator in the afternoon on the day of the storm. In the period after the sunset of the storm day, there is an increase in the density of free electrons and ionospheric irregularities in regions furthest from the geomagnetic equator, when compared to geomagnetically quiet days. When the positioning point is analyzed, it is observed high discrepancies values in planimetry and altimetry at the same position for periods of changes that occurred in the ionosphere, especially for the GPS stations located furthest from the geomagnetic equator in the period after the sunset Sun.

O objetivo deste artigo é analisar a influência de intensas tempestadesgeomagnéticas na ionosfera e no posicionamento por GNSS (GPS). Neste sentido,foram analisados os efeitos da intensa tempestade geomagnética de 20 de novembrode 2003 utilizando dados GPS de algumas estações da RBMC (Rede Brasileira deMonitoramento Contínuo), situadas em diferentes locais na região brasileira, emapas globais da ionosfera. Analisando os resultados se observa um aumento nadensidade de elétrons livres da ionosfera nas regiões mais próximas do equadorgeomagnético no período da tarde no dia da tempestade. No período após o pôr doSol do dia da tempestade, verifica-se um aumento na densidade de elétrons livres ede irregularidades ionosféricas em regiões mais afastadas do equador geomagnético,em comparação com dias geomagneticamente calmos. Quando analisado oposicionamento por ponto, se observa maiores discrepâncias em planimetria ealtimetria no posicionamento para os mesmos períodos em que ocorreram mudanças na ionosfera, principalmente para as estações GPS mais afastadas do equadorgeomagnético no período após o pôr do Sol.
Impact of Geomagnetic Storm in the Ionosphere and GNSS Positioning: Study of case for November 20, 2003 in Brazilian region
Keywords: GNSS; GPS; Ionosphere; Geomagnetic Storm; TEC